Simulation of sales promotions towards buying behavior among university students - Osman, Syuhaily; Chan, Benjamin Yin Fah; Yeoh, Sok Foon (Canadian Center of Science and Education, 2011)
The purpose of this study was to examine the influence of sales promotion on buying behavior among university students. Specifically, University Putra Malaysia (UPM) was chosen as study location. A total of 150 respondents were recruited using systematic random sampling technique. The data were collected using self-administrated questionnaires. This study found that there was no significant difference between gender and buying behavior (t = 1.569, p > 0.05). On the other hand, a there is a significant differences family monthly income and buying behavior (F = 2.597, p <= 0.05). There were significant relationship between attitude towards price discounts (r = 0.351, p <= 0.01), coupons (r = 0.392, p <= 0.01), free samples (r = 0.491, p <= 0.01) and “buy-one-get-one-free” (r = 0.456, p <= 0.01) with buying behavior. Results of Hierarchical Multiple Regression found that free samples and buy-one-get-one-free explained 28.7% variance in buying behaviour of the respondents. The findings of this study would help marketers to understand the types of promotion that significantly influence buying behaviour of the respondents. Hence, this could help marketers in their marketing planning to become more competitive and gain profit.